Community based biogas plant utilizing food waste and cow dung. (2020) - Malik, Wasil; Mohan, Chander; Annachhatre, Ajit P.
Abstract: This research deals with recovery of energy from waste materials such as cow dung (CD) and Food waste (FW). A community scale biogas plant of 5 m 3 capacity was established at IIT Mandi, Himachal Pradesh (HP) and was operated for a period of 160 days. The plant was seeded with CD collected from a Gaushala in Sundernagar (HP). The plant operation stabilized within a startup period of 4–5 weeks. Thereafter, CD feed was gradually replaced by FW by increasing FW:CD ratio from 1:10 to 1:1. The Organic loading rate (OLR) to biogas plant was gradually increased from 0.4 kg VS/m 3 d to 5.2 kg VS/m 3 d within a span of 6 months; concomitantly reducing the hydraulic retention time (HRT) from 63 to 33 days. During the same period, the production of biogas increased from 50 l/d to 1620 l/d with methane percentage of 60–65%. The plant operation was satisfactory at FW:CD ratio of 1:1 and OLR of 5.2 kg VS/m 3 d with biogas production of 1620 l/d corresponding to methane yield of 0.14 m 3 /kg VS removal. This research demonstrates that FW was satisfactorily treated through anaerobic process for the production of biogas as energy.